Globalization and development : current trends - Chakrabarti, Shantanu; Chatterjee, Kingshuk (Institute of Foreign Policy Studies, Calcutta University ; KW Publishers, 2012)
Papers presented at a conference held at New York City during 18-19 November 2010.